2020
DOI: 10.1111/jgh.15068
|View full text |Cite
|
Sign up to set email alerts
|

The reproducibility of skeletal muscle signal intensity on routine magnetic resonance imaging in Crohn's disease

Abstract: Background and Aim Myosteatosis is a prognostic factor in cancer and liver cirrhosis. It can be determined noninvasively using computed tomography or, as shown recently, by magnetic resonance (MR) imaging. The primary aim was to analyze the reproducibility of skeletal muscle signal intensity on routine MR‐enterographies, as indicator of myosteatosis, in Crohn's disease (CD) and to explore the association between skeletal muscle signal intensity at diagnosis with time to intestinal resection. Methods CD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Moreover, screening tools for sarcopenia such as SARC-F (a questionnaire consisting of five questions) as recommended by AWGS and EWGSOP, are not available in patients with IBD [ 4 , 5 , 33 ]. On the other hand, the usefulness of skeletal muscle signal intensity in magnetic resonance imaging (MRI) T1-weighted images for the clinical outcomes in patients with CD has also been reported [ 34 ]. It has been reported that muscle mass in MRI correlates well with lean body mass using a bioelectrical impedance analysis (BIA) method in pediatric patients with UC [ 35 ].…”
Section: Methods and Frequency Of Sarcopenia Assessment In Patients With Ibdmentioning
confidence: 99%
“…Moreover, screening tools for sarcopenia such as SARC-F (a questionnaire consisting of five questions) as recommended by AWGS and EWGSOP, are not available in patients with IBD [ 4 , 5 , 33 ]. On the other hand, the usefulness of skeletal muscle signal intensity in magnetic resonance imaging (MRI) T1-weighted images for the clinical outcomes in patients with CD has also been reported [ 34 ]. It has been reported that muscle mass in MRI correlates well with lean body mass using a bioelectrical impedance analysis (BIA) method in pediatric patients with UC [ 35 ].…”
Section: Methods and Frequency Of Sarcopenia Assessment In Patients With Ibdmentioning
confidence: 99%
“…In the literature, there are only two known smaller scaled studies using different MRI sequences to assess myopenia or myosteatosis in patients with CD. Spooren et al [ 24 ] evaluated T1-weighted fat-saturated post-contrast images in 35 CD patients, while Celentano et al [ 25 ] assessed axial T2-weighted sequences in 31 CD patients. In these studies, myopenia and myosteatosis were associated with a higher rate of postoperative complications and unfavorable disease outcome, indicating potential clinical relevance for these two parameters [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spooren et al [ 24 ] evaluated T1-weighted fat-saturated post-contrast images in 35 CD patients, while Celentano et al [ 25 ] assessed axial T2-weighted sequences in 31 CD patients. In these studies, myopenia and myosteatosis were associated with a higher rate of postoperative complications and unfavorable disease outcome, indicating potential clinical relevance for these two parameters [ 24 , 25 ]. In our cohort of 223 CD patients, we investigated the role of MRI-defined myopenia and myosteatosis with anastomotic leakage, postoperative complications, and recurrence rates based on a homogeneous cohort, including only patients with Crohn’s disease undergone ileocecal resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are only two known smaller scaled studies using different MRI sequences to assess myopenia or myosteatosis in patients with CD. Spooren et al [24] evaluated T1-weighted fatsaturated post-contrast images in 35 CD patients, while Celentano et al [25] assessed axial T2-weighted sequences in 31 CD patients. In these studies, myopenia and myosteatosis were associated with a higher rate of postoperative complications and unfavorable disease outcome, indicating potential clinical relevance for these two parameters [24,25].…”
Section: Discussionmentioning
confidence: 99%